2022
DOI: 10.3390/ijms23179941
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Vesicle-Mediated Mineralization and Osteocytic Regulation of Bone Mineralization

Abstract: Bone mineralization entails two mineralization phases: primary and secondary mineralization. Primary mineralization is achieved when matrix vesicles are secreted by osteoblasts, and thereafter, bone mineral density gradually increases during secondary mineralization. Nearby extracellular phosphate ions (PO43−) flow into the vesicles via membrane transporters and enzymes located on the vesicles’ membranes, while calcium ions (Ca2+), abundant in the tissue fluid, are also transported into the vesicles. The accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 97 publications
(133 reference statements)
0
26
0
Order By: Relevance
“…This occurs as Ca 2+ binds strongly to the inner leaflet of the plasma membrane, which is generally negatively charged, and binds strongly to phosphatidylcholine and phosphatidylserine in the leaflet [36,37]. HA crystals are then formed, which penetrate the plasma membrane to give rise to mineralized nodules [38]. The mineralization of the collagen deposition of calcium phosphate begins from the mineralized nodules that are produced, forming and completing grains [39].…”
Section: Discussionmentioning
confidence: 99%
“…This occurs as Ca 2+ binds strongly to the inner leaflet of the plasma membrane, which is generally negatively charged, and binds strongly to phosphatidylcholine and phosphatidylserine in the leaflet [36,37]. HA crystals are then formed, which penetrate the plasma membrane to give rise to mineralized nodules [38]. The mineralization of the collagen deposition of calcium phosphate begins from the mineralized nodules that are produced, forming and completing grains [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo bone tissue specimens confirmed that some CNHs were present in the bone matrix and within the lacunae. Moreover, CNHs resemble the shape of calcified vesicles [ 25 ]. These results suggest that OBs may have recognized CNHs as resembling the shape of calcified vesicles, incorporated them into the cells, and thus increased the number of calcified vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Further mineral accumulation in the MV is achieved through ion channels and transporters leading to initial nucleation and calcification in the MV. Finally, needle-like hydroxyapatite crystals are released from the MV into the extravesicular fluid, these crystals subsequently being incorporated into the collagen fibril network [14,15]. Some osteoblasts become incorporated into the matrix and turn into immature osteocytes embedded in the fully mineralized and matured matrix [16,17].…”
Section: Molecular Mechanismsmentioning
confidence: 99%